2014
DOI: 10.1038/srep07469
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Ultraviolet Photodetectors Fabricated from ZnO Quantum Dots/Carbon Nanodots Hybrid Films

Abstract: Ultraviolet photodetectors have been fabricated from ZnO quantum dots/carbon nanodots hybrid films, and the introduction of carbon nanodots improves the performance of the photodetectors greatly. The photodetectors can be used to detect very weak ultraviolet signals (as low as 12 nW/cm2). The detectivity and noise equivalent power of the photodetector can reach 3.1 × 1017 cmHz1/2/W and 7.8 × 10−20 W, respectively, both of which are the best values ever reported for ZnO-based photodetectors. The mechanism for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(60 citation statements)
references
References 50 publications
1
59
0
Order By: Relevance
“…The electrons in the conduction band of perovskite then moved downward into the conduction band of the CDs, because the CDs have higher electron affinity (a lower conduction band) than perovskite. Meanwhile, the holes remained in the valance band of perovskite because perovskite has a lower ionization potential (a higher valance band) than the CDs [24,37,46]. This type-II band alignment efficiently enhanced the charge separation at the CsPbBr3/CD interface, enhancing both the photocurrent and responsivity of the photodetector.…”
Section: Working Principle Of the Cspbbr 3 /Cd Composite Photodetectormentioning
confidence: 99%
See 1 more Smart Citation
“…The electrons in the conduction band of perovskite then moved downward into the conduction band of the CDs, because the CDs have higher electron affinity (a lower conduction band) than perovskite. Meanwhile, the holes remained in the valance band of perovskite because perovskite has a lower ionization potential (a higher valance band) than the CDs [24,37,46]. This type-II band alignment efficiently enhanced the charge separation at the CsPbBr3/CD interface, enhancing both the photocurrent and responsivity of the photodetector.…”
Section: Working Principle Of the Cspbbr 3 /Cd Composite Photodetectormentioning
confidence: 99%
“…Xie et al [36] reported a core shell heterojunction photovoltaic device composed of a silicon nanowire array and carbon quantum dots, which reached a power conversion efficiency of 9.10% under AM1.5G irradiation. Guo et al [37], fabricated a photodetector based on zinc oxide quantum dots and CDs, which achieved a detectivity and noise equivalent power of 3.1 × 10 17 cmHz 1/2 /W and 7.8 × 10 −20 W, respectively. Moreover, in photosensing applications, it has been demonstrated that the photoresponsivity of p-n junction based photodetectors can be increased by the use of graphene nanosheets composites [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] The key problem is that some of 7 60 °C under vacuum. In this study, we have successfully fabricated a single precursor using metal-organic framework (MOF) (zeolitic imidazolate framework, ZIF-8) and carbon nanotubes (CNTs).…”
mentioning
confidence: 99%
“…[26][27][28][29] The key problem is that some of 7 60 °C under vacuum. [26][27][28][29] The key problem is that some of 7 60 °C under vacuum.…”
mentioning
confidence: 99%
“…the metal/semiconductor interfaces [10][11][12]23,24]. Due to the ZnO films with surface states and grain boundaries, the interface states will be formed at the interfaces of Au/ZnO during the electrodes fabrication.…”
Section: Resultsmentioning
confidence: 99%